Re-examining parental mediation model for children Internet safety - Teimori, Misha; Hassan, Md Salleh; Bolong, Jusang; Tamam, Ezhar; Adzharuddin, Nor Azura; Daud, Azlina (Universiti Putra Malaysia Press, 2014)
In Malaysia, children spend a lot of time online and are thus often exposed to undesirable experiences. However, little is known about how parents monitor children’s online activities to avert negative exposure. Using the Malaysian context, this study tests the Parental Mediation Model (PMM) developed by the European Kids Online project (a multi-national research network on new media and children). The objective of the study is to test the reliability and validity of measurements of parental mediation of children’s Internet use. A cross-sectional survey was conducted among 420 school children and their parents/guardians. Self-administered questionnaires were employed and exploratory factor analyses and structural equation modelling used to test the model. The results show that the five-factor PMM (technical, monitoring, restrictive, active mediation of Internet safety and active mediation of Internet use) is not applicable to the Malaysian context. Instead, a three-factor model (technical, restrictive monitoring, and active mediation) emerged from the data. Thus, the five-factor PMM of online risks is not a generic construct of dimensions, though the re-constructed three-factor model seems to fit.